Financial performance of public listed private healthcare in Malaysia using data envelopment analysis (DEA) - Bahar, Norsuliha; Ramlan, Rohaizan; Mokhtar, Rashidah; Tasmin, Rosmaini; Dasril, Yosza (Penerbit UTHM, 2020)
The healthcare system in Malaysia has a dual-tiered which are a government-led, also known as public hospital and private hospital that funded by organization or company (Quek, 2014). The public sector wholly subsidized by the government with patients paying only nominal fees for admission to both outpatients and hospitalizations. Thus, the mass of patients led to longer waiting time, heavy workload (Pillay et al., 2011) and overworked (Ren, 2007).